Greening the future: Unveiling the link between industrial structure upgrading and pollution emission in sub-Saharan Africa - Eric Fosu Oteng-Abayie; Emmanuel Duodu; Seth Oduro; Samuel Tawiah Baidoo (Cogent Economics & Finance, 2023)
Industrial structure upgrading (ISU) in sub-Saharan Africa (SSA) has been improving in recent years, making it essential to examine how such upgrading influences pollution emissions in SSA. However, studies concerning the environment in SSA have overlooked this important role. Consequently, achieving the Sustainable Development Goals becomes futile if such critical issues are not given due attention in policy discourse. In light of this, this study examined the effect of ISU on pollution emissions in 28 SSA countries using data from 1980 to 2020 and employed two key measures of ISU as contributions to the literature. Regarding the analysis, the fixed effects, random effects, and feasible generalized least squares estimators and the Dumitrescu and Hurlin (D-H) causality test were employed. The results show that ISU improves the sustainable environment by reducing pollution emissions in SSA by 0.03-0.04%. Furthermore, economic growth (EG) increases pollution emissions by 0.63-0.72%, but after reaching a threshold level of 0.10%, EG reduces pollution emissions by 0.03-0.04%. This confirms the EKC hypothesis in the selected SSAs. The D-H causality analysis also reveals a bidirectional relationship between ISU and pollution emissions. Based on these results, we conclude that upgrading the industrial structure in SSA is crucial for a clean and sustainable environment.
Keywords: 330; sub-Saharan Africa; EKC hypothesis; industrial structure upgrading; pollution emissions; Sustainable Development Goals (SDGs)